Study on the Causes and Effects of Foreign Language Learning Anxiety among Chinese College Students - Su, Yi; Chu, Xiaoyu (Transactions on Social Science, Education and Humanities Research, 2024)
This study delves into the causes and impacts of foreign language learning anxiety among Chinese university students, a topic of significant relevance in the context of China's increasingly globalized educational landscape. Recognizing the crucial role of language proficiency in both academic and professional arenas, this research aims to unravel the multifaceted nature of anxiety experienced by students in learning foreign languages, particularly focusing on the Chinese higher education environment. The research identifies several key factors contributing to language learning anxiety. High-stakes testing culture, traditional pedagogical approaches focusing on rote memorization, and societal emphasis on academic perfection emerge as primary contributors. These elements, coupled with limited opportunities for practical language application, create an environment where anxiety can thrive. The study also notes the influence of personal factors such as students' self-perceptions and previous language learning experiences on their anxiety levels. In terms of impact, the study finds that language learning anxiety significantly hampers students' academic performance, particularly in language proficiency and participation in language classes. Moreover, it extends beyond academic ramifications, affecting students' motivation, attitude towards language learning, and overall psychological well-being. The anxiety experienced in the classroom can lead to broader issues of social withdrawal and diminished self-confidence, with potential long-term implications for students' professional development and global competency. The study's findings underscore the need for educational reforms and the introduction of teaching methods that emphasize interactive learning and communication skills, aimed at reducing anxiety and enhancing language proficiency. The research also highlights the importance of psychological support for students, suggesting that addressing emotional and psychological factors is as crucial as improving pedagogical strategies in foreign language education. In conclusion, this study provides a comprehensive understanding of the causes and impacts of foreign language learning anxiety among Chinese university students. It offers insights for educators, policymakers, and mental health professionals, suggesting a holistic approach to language education that addresses both the academic and emotional needs of students, thereby enhancing the overall quality of language learning experiences in China.